2020
DOI: 10.14336/ad.2019.1125
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Mitochondrial Dysfunction and Neurotransmission Failure in Alzheimer’s Disease

Abstract: Besides extracellular deposition of amyloid beta and formation of phosphorylated tau in the brains of patients with Alzheimer's disease (AD), the pathogenesis of AD is also thought to involve mitochondrial dysfunctions and altered neurotransmission systems. However, none of these components can describe the diverse cognitive, behavioural, and psychiatric symptoms of AD without the pathologies interacting with one another. The purpose of this review is to understand the relationships between mitochondrial and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 275 publications
3
66
0
Order By: Relevance
“…Further, OS exert its effect on the choline recycling from the synapse processes, leading to ACh deficiency [200] . In late stage AD, levels of presynaptic high-affinity choline transporter 1 (CHT1) were observed to be decreased in synaptosomes in the hippocampus and neocortex of humans [201] .…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, OS exert its effect on the choline recycling from the synapse processes, leading to ACh deficiency [200] . In late stage AD, levels of presynaptic high-affinity choline transporter 1 (CHT1) were observed to be decreased in synaptosomes in the hippocampus and neocortex of humans [201] .…”
Section: Oxidative Stressmentioning
confidence: 99%
“…For instance, it was observed that the expression and function of key enzymes in the glycolytic cascade is reduced with high ROS levels [32] , [216] , [217] . Energy alterations were also linked to a decreased functionality of enzymes related to TCA cycle, which lead neurons to a hypometabolic state [200] , [218] [222] . High Cerebrospinal fluid pyruvate and lactate has been widely reported in AD patients compared with healthy elderly controls [223] .…”
Section: Energy Metabolismmentioning
confidence: 99%
“…The combination of pathological and clinical features, however, does not overcome the issue of defining the disease—defining a “disease” requires identification of the causes [ 15 ]. It has long been thought that AD is caused by the deposition of amyloid-β [ 3 , 4 ]. However, amyloid-β can be found in healthy older subjects [ 16 , 17 ], and there seems to be little to no correlation between amyloid load and the degree of cognitive decline in AD patients [ 18 , 19 ].…”
Section: The Need For Interdisciplinary Research In Understanding Admentioning
confidence: 99%
“…Other markers like tau and neurofibrillary tangles correlate better to cognitive decline in AD patients, yet this still does not establish a causative role, and may simply reflect a pathological feature of another causative process [ 15 ]. This lack of understanding of the causes of AD brings difficulties in itself, yet it is further compounded by the fact that it prevents the development of good experimental models [ 3 , 4 ]. Transgenic mice are one of the most widely used models in AD, and their use has been extensively discussed by Drummond and Wisniewski [ 20 ], yet they and others have noted issues in the lack of consistency of these experimental models or their lack of relevance (e.g., dependence on familial AD mutations but most cases tend to be sporadic).…”
Section: The Need For Interdisciplinary Research In Understanding Admentioning
confidence: 99%
See 1 more Smart Citation